Endometrial scratching during hysteroscopy in women undergoing in vitro fertilization: a systematic review and meta-analysis - Papanikolaou, Evangelos; Peitsidis, Nikolaos; Tsakiridis, Ioannis; Michos, Georgios; Skalias, Antonios; Patoulias, Dimitrios; Poutoglidis, Alexandros; Mamopoulos, Apostolos; Athanasiadis, Apostolos; Grimpizis, Grigorios; Najdecki, Robert (Frontiers in Surgery, 2023)
Objective. -Endometrial scratching (ES) during hysteroscopy before embryotransfer (ET) remains doubtable on whether it benefits the reproductive outcomes. The optimal technique is not clear and repeated implantation failure as a challenging field in in vitro fertilization (IVF) seems to be the springboard for clinicians to test its effectiveness.Methods. -Medline, PMC, ScienceDirect, Scopus, CENTRAL, Google Scholar were searched from their inception up to April 2023 for studies to evaluate the effectiveness of adding endometrial scratching during hysteroscopy before ET.Results. -The initial search yielded 959 references, while 12 eligible studies were included in the analyses, involving 2,213 patients. We found that hysteroscopy and concurrent ES before ET resulted in a statistically significant improvement in clinical pregnancy rate (CPR) (RR = 1.50, [95% CI 1.30-1.74], p < 0.0001) and live birth rate (LBR) (RR = 1.67, [95% CI 1.30-2.15], p < 0.0001) with no statistically significant difference on miscarriage rate (RR = 0.80 [95% CI 0.52-1.22], p=0.30)Conclusion. -Our meta-analysis suggests that hysteroscopy with concurrent ES may be offered in IVF before ET as a potentially improving manipulation. Future randomized trials comparing different patient groups would also provide more precise data on that issue, to clarify specific criteria in the selection of patients.